Building on the past: Refining our current understanding of Lapita stilt structures. Issue 3 (2nd September 2022) - Hogg, Nicholas W.S.; Chen, Yi-lin E.; Summerhayes, Glenn R.; Boswijk, Gretel; Manning, Sturt W.; Hogg, Alan G.; Gosden, Chris
Abstract: This paper reviews our current knowledge of Lapita stilt structures in the Bismarck Archipelago, Papua New Guinea, and contributes new data from the analysis of a wooden post belonging to a Lapita-era stilt structure identified in the site of Adwe in the Arawe Islands. Via taxonomic analysis, the wooden post is identified as Intsia bijuga (Moluccan ironwood or Pacific teak), a saltwater-resistant species that would have proven to be a highly durable construction material. The selective usage of sturdy timber including Intsia bijuga, cf. Cordia subcordata, Diospyros sp., cf. Terminalia catappa and Calophyllum inophyllum as building materials at various Lapita sites, suggests that the Lapita populations had a clear understanding of locally available timber resources. This paper also details a world-first attempt at radiocarbon wiggle-match dating a Lapita-age wooden artefact.